2003
DOI: 10.1088/0960-1317/14/2/012
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic generation of microvortex patterns in a microchannel liquid flow

Abstract: The technology developed for micropatterning the electric surface charge to be negative, positive or neutral enables the realization of complex liquid flows in simple microchannels. A commercial CFD code is utilized to numerically simulate a variety of electrokinetically-generated liquid flows in a straight and uniform microchannel due to non-uniform surface charge distribution under an externally applied, steady electric field. We present design methodologies to electrokinetically drive vortical flows in any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…For example, various researchers have performed theoretical studies of electroosmotic flows in 2-D microchannels driven by time-dependent zeta potentials or a time-dependent external electric field, and have demonstrated that chaotic advection can be induced by time-wise periodic alternations of the zeta potential and can improve the mixing performance as a result (Qian and Bau 2002); these are to be described in the section of active mixing scheme. In addition, chaotic advection or transverse flows can also be induced in three-dimensional steady electroosmotic flows with time-independent zeta potentials through the use of specific surface charge patterning configurations (Ajdari 1996(Ajdari , 2001Erickson and Li 2003;Ng et al 2004;Yang and Chang 2004;Biddiss et al 2004;Chang and Yang 2006). Generally, heterogeneous surface charges or non-uniform time-independent zeta potentials are obtained through passive approaches such as coating the microchannel walls with different materials (Liu et al 2000;Stroock et al 2000;Fushinobu and Nakata 2005) or applying suitable surface-chemistry treatments (Hau et al 2003;Krishnamoorthy et al 2006).…”
Section: Heterogeneous Surface Charge Patterning Enhanced Electroosmomentioning
confidence: 99%
“…For example, various researchers have performed theoretical studies of electroosmotic flows in 2-D microchannels driven by time-dependent zeta potentials or a time-dependent external electric field, and have demonstrated that chaotic advection can be induced by time-wise periodic alternations of the zeta potential and can improve the mixing performance as a result (Qian and Bau 2002); these are to be described in the section of active mixing scheme. In addition, chaotic advection or transverse flows can also be induced in three-dimensional steady electroosmotic flows with time-independent zeta potentials through the use of specific surface charge patterning configurations (Ajdari 1996(Ajdari , 2001Erickson and Li 2003;Ng et al 2004;Yang and Chang 2004;Biddiss et al 2004;Chang and Yang 2006). Generally, heterogeneous surface charges or non-uniform time-independent zeta potentials are obtained through passive approaches such as coating the microchannel walls with different materials (Liu et al 2000;Stroock et al 2000;Fushinobu and Nakata 2005) or applying suitable surface-chemistry treatments (Hau et al 2003;Krishnamoorthy et al 2006).…”
Section: Heterogeneous Surface Charge Patterning Enhanced Electroosmomentioning
confidence: 99%
“…The surface-charge pattern for generating a single out-of-plane spanwise vortex consists of a positively or negatively charged region on either the top or bottom channel surface with the corresponding region on the opposite surface carrying the opposite charge [18]. The active area is placed at the center, while the rest of the microchannel surface is kept neutral.…”
Section: Out-of-plane Single Vortexmentioning
confidence: 99%
“…The four coefficients , , , and can now be determined by substituting the four boundary conditions (12) and (14) into (9) and (10) Substitution of the coefficients in (15) into (7) yields (16) with (17a) and (17b) Thus, the stream function is given by (18) as shown at the bottom of the page and the velocity components and are readily available, as shown in (19) at the bottom of the page. By substituting the velocity solution (19) into the boundary conditions (4)- (6), the boundary condition (6) can be exactly satisfied.…”
Section: A Theoretical Analysismentioning
confidence: 99%
“…A number of different methods utilizing these principles have been applied to enhance mixing in microfluidic devices by creating or attempting to create chaotic flow fields. These may be roughly divided into passive type mixers such as patterned surfaces (Stroock et al 2002a, b;Wang et al 2003), sinusoidal and serpentine flows (Liu et al 2004;Song 2003;Liu 2000), and split and recombine flows (Hessel 2003;Schonfeld et al 2004;Mae 2004); and active mixers which includes exploitation of secondary flows (Solomon and Mezic 2003;Solomon et al 1998;Pathak et al 2004;Groisman and Steinberg 2001), oscillatory flow (Truesdell et al 2003;Okkels and Tabeling 2004;Niu and Lee 2003;Bottausci et al 2004;Glasgow et al 2004), and a vast array of electrokinetic flow methods (Lin 2004;Oddy et al 2001;Fu et al 2005;Jacobson et al 1999;Lin et al 2002;Ng et al 2004;Shin et al 2005;Sundaram and Tafti 2004;Wang et al 2004;Wu and Liu 2005).…”
Section: Introductionmentioning
confidence: 99%